Kajian Kualitas Hadits tentang Risywah dalam Perspektif Ulumul Hadits : Analisis Sanad dan Matan - Okki Dwi Cahya; Romlah Abubakar Askar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the quality of hadiths concerning risywah (bribery) through the classical hadith sciences perspective, focusing on sanad (chain of transmission) and Matan (textual content) criticism. Using a qualitative approach, the research traces the transmission routes and analyzes the content of relevant hadiths sourced from primary collections such as the Kutub Sittah and contemporary scholarly works. The analysis reveals that most hadiths on risywah exhibit significant weaknesses in their sanad, including inconsistencies in transmission chains (idhthirāb), questionable credibility of key narrators, and the presence of unidentified narrators (majhūl al-hāl). Additionally, variations in wording and potential distortions in the matan raise doubts about the authenticity of the hadith content. Nevertheless, some hadiths with stronger sanad, such as those narrated by Abdullah bin 'Amr and Abu Hurairah, serve as solid foundations for reinforcing the prohibition of risywah. The study underscores the necessity of a holistic approach in hadith criticism that integrates sanad verification, Matan analysis, and historical contextualization to preserve the integrity of Islamic legal sources and recommends caution in utilizing problematic hadiths related to risywah.